Pendekatan Agile Software Development dalam Sistem Informasi Berbasis Web untuk Optimalisasi Manajemen Data Iklan - Herawati, Afni Kurnia; Putri, Dwi Ismiyana (Jurnal Informatika Terpadu, 2025)
Advertising data management in Emtek Digital's Open Marketplace (OMP) division continues to face such as fragmented documentation, the risk of data duplication, and limited transparency in real-time ad performance tracking. These issues reduce strategic effectiveness and slow down the decision-making process. This study aims to develop an integrated information system that can improve efficiency, accuracy, and transparency in advertising data management. Using the Agile Software Development method, a web-based system was designed to be adaptive to changing user needs and equipped with data automation, report validation, and user and partner management features. Testing was conducted using the Blackbox and User Acceptance Test (UAT) methods, obtaining an average score of 83.3% in the “Very Good” category. These results indicate that the developed system is feasible for implementation and capable of supporting fast and accurate data-driven decision-making. Unlike the previous non-integrated system, this research introduces innovations in integration and reporting process automation, thereby improving the efficiency and transparency of advertising data management.